Clinical significance and new detection system of autoantibodies in myositis with interstitial lung disease. (July 2016) - Nakashima, R; Hosono, Y; Mimori, T
Anti-aminoacyl-tRNA synthetase (ARS) and anti-melanoma differentiation-associated gene 5 ( MDA5 ) antibodies are closely associated with interstitial lung disease in polymyositis and dermatomyositis. Anti-ARS-positive patients develop common clinical characteristics termed anti-synthetase syndrome and share a common clinical course, in which they respond well to initial treatment with glucocorticoids but in which disease tends to recur when glucocorticoids are tapered. Anti- MDA5 antibody is associated with rapidly progressive interstitial lung disease and poor prognosis, particularly in Asia. Therefore, intensive immunosuppressive therapy is required for anti- MDA5 -positive patients from the early phase of the disease. New enzyme-linked immunosorbent assays to detect anti-ARS and anti- MDA5 antibodies have recently been established and are suggested to be efficient and useful. These assays are expected to be widely applied in daily practice.